Rediscovering the Double Friedel–Crafts Acylation: An Expedient Entry to Phenanthrene-9,10-diones - Crosta, Nicoletta; Müller, Sebastian; Gradl, Dietmar; Masters, Kye-Simeon; Bräse, Stefan (Synlett, 2013)
The double Friedel–Crafts acylation of readily accessible biaryls with oxalyl chloride delivers the respective phenanthrene-9,10-diones, providing an alternative to the traditional methods, which require harsh oxidizing conditions and multistep sequences. This simple method allows the synthesis of various symmetrical and non-symmetrical targets, and is even effective for the synthesis of the parent ring system from (unactivated) biphenyl.
Keywords: cyclization; electrophilic aromatic; substitution; fused-ring systems; Friedel–Crafts acylation; phenanthrene-9,10-diones